The distinctive pattern of declarative memories in autism spectrum disorder: Further evidence of episodic memory constraints - Souza, C. (2023)
This study examines declarative memory retrieval in ASD depending on the availability and access to stored conceptual knowledge. Fifteen autistic participants and a matched control group of 18 typically-developed (TD) volunteers completed a Remember-Know paradigm manipulated by encoding-type (categorical, perceptual) and item-typicality (high-typical, low-typical). The autistic group showed worse and slower recognition and less recollection but equivalent familiarity-based memories compared to TDs. Notably, low-typical items did not improve their memories as they did for TDs, likely due to difficulties in matching low-fit information to the stored schema. Results suggest that memory decline in ASD may derive from the episodic system and its dynamics with the semantic system. These findings may inform interventional strategies for enhancing learning abilities in ASD.